Sustaining our rural allied health workforce: experiences and impacts of the allied health rural generalist pathway - Alison Dymmott; Stacey George; Narelle Campbell; Chris Brebner (BMC, 2024)
Abstract Introduction Rural and remote communities face significant disadvantages accessing health services and have a high risk of poor health outcomes. Workforce challenges in these areas are multifaceted, with allied health professionals requiring broad skills and knowledge to provide vital services to local communities. To develop the expertise for rural and remote practice, the allied health rural generalist pathway (AHRGP) was introduced to develop and recognise specialist skills and knowledge required for rural and remote practice, however the experiences of professionals has not been explored. This study gained the experiences and perceptions of allied health professionals undertaking the pathway as well as their clinical supervisors, line managers, profession leads and consumer representatives. Methods A qualitative study was undertaken drawing on pragmatic approaches across four research phases. This study was one component of a larger mixed methods study investigating the experience, impact and outcomes of the AHRGP across six regional Local Health Networks in South Australia (SA). Interviews, surveys and focus groups were conducted to explore the perceptions and experiences of participants. Data was analysed thematically across participant groups and research phases. Results A total of 54 participants including 15 trainees, 13 line managers, nine clinical supervisors, six profession leads, four program managers and seven consumer representatives informed this study. Five themes were generated from the data; gaining broad skills and knowledge for rural practice, finding the time to manage the pathway, implementing learning into practice, the AHRGP impacts the whole team and confident, consistent, skilled allied health professionals positively impact consumers. Conclusion The AHRGP is offering allied health professionals the opportunity to develop skills and knowledge for rural and remote practice. It is also having positive impacts on individuals' ability to manage complexity and solve problems. Findings indicated consumers and organisations benefited through the provision of more accessible, consistent, and high quality services provided by trainees. Trainees faced challenges finding the time to manage study and to implement learning into practice. Organisations would benefit from clearer support structures and resourcing to support the pathway into the future. Incentives and career advancement opportunities for graduates would strengthen the overall value of the AHRPG.